2013
DOI: 10.1109/tbme.2013.2241059
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Band of the Resting Electroencephalogram Under Pulsed and Continuous Radio Frequency Exposures

Abstract: The effect of GSM-like electromagnetic fields with the resting electroencephalogram (EEG) alpha band activity was investigated in a double-blind cross-over experimental paradigm, testing the hypothesis that pulsed but not continuous radio frequency (RF) exposure would affect alpha activity, and the hypothesis that GSM-like pulsed low frequency fields would affect alpha. Seventy-two healthy volunteers attended a single recording session where the eyes open resting EEG activity was recorded. Four exposure interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
3
34
2
Order By: Relevance
“…The above findings however are not consistent with results from a large and well-controlled study by Perentos et al (2013) who investigated the effects on the EEG of GSM-like signals (900 Mz, pulsed at 2.1,8.3 and 217 Hz), continuous RF with the same carrier frequency, ELF-EMF with the same pulsing rates as the GSM signal and sham exposure. They found that both GSM-like RF and continuous RF had significant and comparable effects on the EEG but ELF did not.…”
Section: Discussioncontrasting
confidence: 86%
“…The above findings however are not consistent with results from a large and well-controlled study by Perentos et al (2013) who investigated the effects on the EEG of GSM-like signals (900 Mz, pulsed at 2.1,8.3 and 217 Hz), continuous RF with the same carrier frequency, ELF-EMF with the same pulsing rates as the GSM signal and sham exposure. They found that both GSM-like RF and continuous RF had significant and comparable effects on the EEG but ELF did not.…”
Section: Discussioncontrasting
confidence: 86%
“…Perentos et al 64 observed a suppression of the global alpha band (8-12.75 Hz) activity under a 20-min low-level Real GSM-like extremely low frequency (ranging from direct current to at least 40 kHz) exposure compared to Sham in the exposed hemisphere only. In their follow-up study, 63 it was found that this decrease in alpha band power was present also both under pulse modulated and continuous GSM RF exposure. Another article 56 reported a statistically significant decrease of the alpha band spectral power in the post-exposure session after GSM RF exposure.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of waking EEG, the effect of RF (considering GSM systems) has been predominantly shown to increase alpha band power, [57][58][59][60][61] although some reductions of alpha band power have also been reported. 56,[62][63][64] In a single-blind study by D'Costa et al, 62 during a single 25-min Real GSM exposure, statistically significant decreases were found in EEG power at 8 Hz and 9 Hz in the occipital region, and at 7 Hz and 9 Hz in both the occipital end central recording sites compared to Sham exposure. Perentos et al 64 observed a suppression of the global alpha band (8-12.75 Hz) activity under a 20-min low-level Real GSM-like extremely low frequency (ranging from direct current to at least 40 kHz) exposure compared to Sham in the exposed hemisphere only.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, data reported by some authors showed an increase in EEG power in the alpha frequency band (Cook et al 2004;Croft et al 2002Croft et al , 2008Croft et al , 2010Curcio et al 2005;Hinrikus et al 2008;Huber et al 2002;Kramarenko and Tan 2003;Regel et al 2007;Reiser et al 1995), whereas other studies reported a decrease in EEG power or coherence in the alpha band (Maby et al 2006;Perentos et al 2013;Vecchio et al 2007Vecchio et al , 2010Vecchio et al , 2012. Finally, other studies failed to show an effect on EEG power in the alpha bands (D'Costa 2003; Hietanen et al 2000;Röschke and Mann, 1997;Perentos et al 2007).…”
mentioning
confidence: 96%